Optimalisasi Penggunaan Ms.Word Dalam Penulisan Karya Ilmiah - Liza Fitriana; R Ramli; Stephanus Priyowidodo (LPPM STIKOM Tunas Bangsa, 2021)
MS. Word is one of many application that is widely used by people in writing paper using computers. According to its function, many features in MS. Word could be used in manipulating words in various form. From all features that are available in MS. Word, there are some features that are rarely known or used by people. On this basis, we, the Universitas Harapan Medan Devotion Service Team conducted socialization activities on Optimization of Using MS. Word in Writing Paper.